(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
In many countries of Europe rabbit meat is consumed for its nutritional characteristics, (Dalle Zotte, 2014; Hernández and Gondret, 2006). Since the ban of the use of antibiotic as growth promoter, natural substances have been studied as alternative with antioxidant, anti-inflammatory, antimicrobic and antiviral properties. The aim was to evaluate the effect of a dietary supplementation with natural extract mixture in growing rabbit on growth performances, carcass characteristics and Longissimus lumborum (LL) muscle parameters. The trial was performed at the Research Institute for Animal Production (Nitra, Slovak Republic) and lasted 42 days. At 35 days of age, 144 New Zealand White rabbits were randomly selected and divided in 3 experimental groups (4 rabbits/cage). The first fed a basal diet, the second (T1) and the third one (T2) received 0.3% and 0.6% of natural extract mixture, containing polyphenols from plants and seaweeds. Dietary integration with natural extract improve (P<0.05) growth performances (ADG, FI and FC) in T1 group. The fatty acid composition of LL muscle was positively affected (P=0.037) by natural extract supplementation with an increase of n-3 FA in T2 group than other treatments. Cholesterol content tended to be lower in T2 group (P=0.082) than T1 and C group (24.8 mg/100g T2 vs 34.6 mg/100g T1 vs 33.2 mg/100g C). Sensory analysis revealed that only the aroma was affected (P<0.05) by dietary treatments. Overall these results highlight that dietary supplementation with natural extract mixture, containing polyphenols from plants and seaweeds enhance growth performances, carcass weight, improving LL muscle nutritional parameters.